Phenotypic and molecular characterization of quinolone resistance of enteropathogens isolated from diarrhea in young children in Koula-Moutou/Gabon. Issue 1 (1st January 2021) - Mabika Mabika, Rolande; Mounioko, Franck; Souza, Alain; Yala, Jean Fabrice
ABSTRACT: In the face of the growing phenomenon of multidrug-resistant bacteria, studies on the sensitivity profiles of enteric pathogens are required to better manage the remaining antibiotic capital. The objective of this study was to investigate the sensitivity and to determine the genetic basis of quinolone-resistant enteric diarrheal pathogens isolated from children in the city of Koula-Moutou, Gabon. Thirty strains of the Salmonella genera, five strains of Shigella and two strains of Yersinia (2) were analyzed. The Kirby–Bauer method was used to determine the sensitivity of these isolates to five molecules in the quinolone family. The presence of chromosomal ( gyrA ) and plasmid (PMQR) quinolone resistance genes, including the QNR complex ( qnrA, qnrB, and qnrS ) were investigated by PCR. These enteric pathogens exhibited high levels of resistance to quinolones, particularly ofloxacin (100%) and ciprofloxacin (97.3%). Most isolates of Salmonella were found to be resistant to nalidixic acid (86.7%), however all isolates of the Shigella and Yersinia genera were susceptible to this antibiotic. Among the 37 strains, 21.6% had the gyrA gene, 13.5% had the qnrB and qnrS genes but the qnrA gene was not detected. Enteric pathogens isolated from the diarrheal feces of the children in Koula-Moutou exhibited high levels of phenotypic resistance to quinolones. This resistance is especially due to mutations occurring on the chromosomal determinant gyrA which also played a role in the reduced sensitivity of these strains to fluoroquinolones. The resistance is also linked to a lesser extent to the acquisition of the PMQR genes, notably qnrB and qnrS . In conclusion, this study highlights the high prevalence rate of enteric pathogens isolated from diarrheal feces of children in Gabon and shows the presence of the QNR complex genes ( qnrB and qnrS ) in the strains.